CLINICAL SIGNIFICANCE OF ELEVATED ANKLE-BRACHIAL INDEX DIFFERS DEPENDING ON THE AMOUNT OF APPENDICULAR MUSCLE MASS: THE J-SHIPP AND THE NAGAHAMA STUDY. (June 2018) - Tabara, Y.; Igase, M.; Setoh, K.; Ohyagi, Y.; Miki, T.; Nakayama, T.; Kohara, K.; Matsuda, F.
Abstract : Objective: Low ankle-brachial index (ABI) is associated with cardiovascular risk factors. In contrast, the clinical implication of high ABI is less understood, though several cross-sectional studies reported that high ABI was associated with cardiovascular risk factors. From our preceding study, we suspected that body composition may be a determinant for high ABI, and consequently modulate the clinical significance of high ABI. Design and method: Datasets of two studies employing independent cohorts, the anti-aging study cohort (n = 1, 765, 65 ± 9 years) and Nagahama study (n = 8, 039, 58 ± 13 years), were analyzed in this study, in which appendicular muscle mass was measured by computed tomography and bioelectrical impedance analysis, respectively. Brachial and ankle blood pressure were measured using a cuff-oscillometric method. Results: In the anti-aging study cohort, there was a significant correlation between the thigh muscle cross-sectional area (CSA) and ABI (r = 0.310, p < 0.001). The association of thigh muscle area (β = 0.387, p < 0.001), but not fat area, was independent of body mass index (p = 0.662) and other possible covariates, including systolic brachial blood pressure (p = 0.054), carotid hypertrophy (p = 0.559), and arterial stiffness (β = 0.102, p = 0.001). Although there was a significant sex-differences in the thigh muscle area, muscle CSA was identified as an independent determinant for ABI (β = 0.286, p < 0.001, VIF = 4.87) even in a sex (women: β = −0.087, p = 0.055, VIF = 4.19) included regression model. This positive association was replicated in the Nagahama cohort. When the subjects were subdivided by 75 percentiles of ABI and appendicular muscle mass, multinomial logistic regression analysis identified insulin resistance as an independent determinant for elevated ABI with normal muscle mass (coefficient = 0.134, p = 0.010), whereas insulin resistance was inversely associated with elevated ABI in cases with high muscle mass (coefficient = −0.268, p = 0.001). Conclusions: Appendicular muscle mass was a strong determinant for ABI. The clinical background, particularly insulin resistance, of individuals with elevated ABI might differ based on the amount of muscle mass.